Answer:
depends, if he has 6 then he still has 6
if he gave her 3 of his six, then ate the pies, he has 3
Step-by-step explanation:
Answer:-5
Step-by-step explanation:
2x+7-x+12=14
x+19=14
x=-5
Answer:
The explicit formula for the given expression is
.
Step-by-step explanation:
The given sequence is
-7, -4, -1, 2, 5
The difference between two consecutive terms is same, therefore the given sequence is an arithmetic sequence.
The first term of the given AP is -7 and the common difference is
![-4-(-7)=-4+7=3](https://tex.z-dn.net/?f=-4-%28-7%29%3D-4%2B7%3D3)
The explicit formula for an AP is
![a_n=a+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da%2B%28n-1%29d)
Where, a is first term, d is common difference and n is number of terms.
Substitute a=-7 and d=3 in the above equation.
![a_n=-7+(n-1)3](https://tex.z-dn.net/?f=a_n%3D-7%2B%28n-1%293)
![a_n=-7+3n-3](https://tex.z-dn.net/?f=a_n%3D-7%2B3n-3)
![a_n=-10+3n](https://tex.z-dn.net/?f=a_n%3D-10%2B3n)
Therefore the explicit formula for the given expression is
.
Answer:
5v^2x + 4
Step-by-step explanation:
I'm not sure but i hope this help's
The coefficient of the second term is 18.
What you do is you FOIL the terms: